A Pharmacogenetically Guided Acenocoumarol Dosing Algorithm for Chilean Patients: A Discovery Cohort Study - Roco, Angela; Nieto, Elena; Suárez, Marcelo; Rojo, Mario; Bertoglia, Maria Paz; Verón, Gabriel; Tamayo, Francisca; Arredondo, Annabella; Cruz, Daniela; Muñoz, Jessica; Bravo, Gabriela; Salas, Patricio; et al. (Frontiers in Pharmacology, 2020)
Background: Vitamin K antagonists (VKA) are used as prophylaxis for thromboembolic events in patients with cardiovascular diseases. The most common VKA are warfarin and acenocoumarol. These drugs have a narrow therapeutic margin and high inter-individual response variability due to clinical and pharmacogenetic variables. Objective: Develop an algorithm comprised of clinical and genetic factors to explain variability in therapeutic dose of acenocoumarol among Chilean patients. Methodology: DNA was obtained from 304 patients as a discovery cohort with INR range 2.0 – 3.0. Non-genetic (demographic and clinical) variables were also recorded. Genotype analyses were performed using real-time PCR for VKORC1 (rs9923231), VKORC1 (rs7294), GGCx (rs11676382), CYP4F2 (rs2108622), ABCB1 (rs1045642), CYP2C9*2 (rs1799853), ApoE (rs429358) and CYP2C9*3 (rs1057910). Results: The clinical variables that significantly influenced weekly therapeutic dose of VKA were: age, sex, BMI, and initial INR, collectively accounting for 19% of the variability, and the genetic variables with a significant impact were VKORC1 (rs9923231), CYP2C9*2 (rs1799853), and CYP2C9*3 (rs1057910), explaining for another 37% of the variability. Conclusion: We developed an algorithm that explains 49.99% of the variability in therapeutic VKA dosage in the Chilean population studied. Factors in that significantly affected dosage included VKORC1, CYP2C9*2, and CYP2C9*3 polymorphisms, as well as age, sex, BMI, and initial INR.